Fish Diversity In Relation To Physico-Chemical Characteristics of Kamala Basin of Darbhanga District, Bihar, India - Prabhahar, C (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT The fish community of the Kamala basin reservoir in relation to physico-chemical parameters was studied by quarterly samples collected from June-2010 to May-2011. The water of the reservoir is used for producing electricity, fishery and livestock activities. Fish collections were done with gillnets of standardized dimensions with several mesh sizes. 35 fish fauna identified during the study belongs to 22 family few includes Cyprinidae 31 species, Cobitidae 4 species, Ophiocephalidae 4 species, Bagridae 6 species etc. Besides identification, relative occurrence and economic importance of fishes are discussed. All fishes are useful as commercial, predatory food fishes, which are useful as ornamental and larvicidal fishes. The species diversity is peak in post monsoon, coinciding with favorable conditions such as sufficient water and ample food resources. The diversity was low in pre-monsoon probably due to the shrinkage of the water spread of the reservoir. The high value of dissolved oxygen coupled with low biochemical oxygen demand and other nutrient levels indicate that the water body is moderately oligotrophic in nature. The factors responsible for declining population of fish species is discussed in detail. To save this diversity and to develop a sustainable fishery practices and proper documentation leading to diversity information system is an urgent need.